Staffing the Hospitals : An Urgent National Need - Great Britain. Ministry of Labour and National Service. (London : Published for the Minister of health, the Secrerary of State for Scotland and the Minister of labour and national service by H.M.S.O., 1945)
1945 1945 1940s 20 pages 19 Area Addresses Tel. Nos. London Spencer House, 27, St. James's Place, London, S W.1. Regent 6757 Aberdeen 6, Queens Gate, Aberdeen Aberdeen 4646-7 Bradford Britannia House, Broadway, Leeds Road, Bradford. Bradford 11837-8 Birmingham 237-239, Broad Street, Birmingham, 1 Midland 6021-8 Brighton 3. Lansdowne Road. Hove, Sussex Hove 1042 Bristol 46, Pembroke Road, Clifton, Bristol, 8 Bristol 34014 Cambridge 16, Station Road, Cambridge Cambridge 56950 Cardiff 9, Dumfries Place, Cardiff Cardiff 7477 Colchester 31, St. John Street, Colchester, Essex. Colchester 4463-6 Coventry 12, Manor Road, Coventry Coventry 60681 Dundee 30, Meadowside, Dundee, Angus Dundee 3073-4 Edinburgh 11, Rothesay Terrace, Edinburgh, 3 Edinburgh 22121 Glasgow 450, Sauchiehall Street, Glasgow, C.3 Douglas 7161 Hull Mail Buildings, Jamieson Street, Hull Hull 16261 Leeds 15-19, The Headrow, Leeds, 1 Leeds 31496 Leicester 10, Salisbury Road, Leicester Leicester 23418-9 Liverpool Cotton Exchange, Bixteth Street, Liverpool. Central 2625-8 Manchester 47, Corporation Street, Manchester, 4 Deansgate 5721 Newcastle-on-Tyne. 153, Barras Bridge, Newcastle-on-Tyne, 2. Newcastle-on-Tyne 22477-9 Norwich 5, Queen Street, Norwich, Norfolk Norwich 20571-4 Nottingham 40, Parliament Street, Nottingham Nottingham 44361 Oxford Exeter College Annexe, Turl Street, Oxford. Oxford 48915 Plymouth 7, Thorn Hill Villas, Mannamead, Plymouth Plymouth 60323 Preston 9, West Cliffe Terrace, Preston, Lanes. Preston 3614 Reading Oxford Street Chambers, Oxford Road, Reading, Berks. Reading 4274 Sheffield The White Building, Fitzallan Square, Sheffield, 1. Sheffield 26671 Southampton 16, Westwood Road, Southampton Southampton 74084 Swansea Metropole Chambers, Salubrious Passage, Wind Street, Swansea. Swansea 4184 Wolverhampton 3, Queen Street, Wolverhampton Wolverhampton 23407 Wrexham 30, Grosvenor Road, Wrexham Wrexham 3235 126/TG/RES/X/1036A/4